Pengaruh Kompetensi dan Disiplin kerja Terhadap Kinerja Pegawai Dikantor Dinas Perhubungan Kota Lubuklinggau - Fitri Arnita Purindra; Hardi Mulyono; Wisdaliya Maya Sari (UNIVED Press, 2024)
This study aims to determine the effect of work discipline competence on employee performance at the Office of Transportation Office of Lubuklinggau. The type of research used was a quantitative approach. The focus of the research was to determine the effect of competence and work discipline on employee performance. The results showed that there was an effect of competence (X1) on employee performance (Y), there was an influence of work discipline (X2) on employee performance (Y), and there was an influence of competence (X1) and work discipline (X2) on employee performance (Y) at Lubuklinggau Transportation Office. Kata kunci: Kompetensi, Disiplin kerja, Kinerja Pegawai